2022
DOI: 10.35877/jetech750
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Types of Occupational Health and Safety Risk (K3) in Erection Work

Abstract: Infrastructure Development Certification of Human Resources Deputy Building 3 is planned as one of the supporting facilities to improve the quality of human resources, especially in the environment Badan Siber dan Sandi Negara, Indonesia. The purpose of this study is to find out the results of the analysis of the types of risk of K3 in the erection work in Project Pembangunan Infrastruktur Sertifikasi SDM Badan Siber dan Sandi Negara and know the types of K3 risks that play the most role that occur in erection… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…In previous studies, there have been many studies on risk measurement in manufacturing companies using various methods (Hidayah et al, 2022;Mawiestin et al, 2021;Ridwan et al, 2022;Sobirin et al, 2022). Previous research on COVID-19 risk assessment within the service sector has indicated a widespread vulnerability of employees and clients to the virus, underscoring the urgency of implementing comprehensive risk management strategies.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In previous studies, there have been many studies on risk measurement in manufacturing companies using various methods (Hidayah et al, 2022;Mawiestin et al, 2021;Ridwan et al, 2022;Sobirin et al, 2022). Previous research on COVID-19 risk assessment within the service sector has indicated a widespread vulnerability of employees and clients to the virus, underscoring the urgency of implementing comprehensive risk management strategies.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, previous research conducted at (Persero) UPK PLTU Tambora during COVID-19 shows that OHS is very important to be implemented in companies with a purposive sampling stage in sampling (Suprianto et al, 2021). However, there have not been many studies related to measuring the level of risk of human resources due to COVID-19 in power plants with a high level of risk (Hidayah et al, 2022;Mawiestin et al, 2021;Ridwan et al, 2022;Sobirin et al, 2022). The risks can be interpreted as all possibilities that can occur and have impacts and consequences.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation